2014
DOI: 10.1111/anae.12748
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and inter‐centre standardisation of thromboelastography (TEG®)

Abstract: SummaryThromboelastography is used for assessment of coagulation and to guide administration of blood products peri-operatively. There is currently no method of standardisation in the UK, nor an approved method of proving quality. We investigated the reproducibility of thromboelastography by testing whole blood with no coagulation abnormality in three phases. Where a single operator performed multiple assays on the same blood sample at a single location, we found considerable variation, with 21% of R-and 25% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…42 This is thought to be due to age related changes and variations in phenotypes of hemostasis seen across populations, as well as instrument operator variability. Thus, generic reference ranges may not be applicable to individual centers and should be locally produced.…”
Section: Assay Interpretationmentioning
confidence: 99%
“…42 This is thought to be due to age related changes and variations in phenotypes of hemostasis seen across populations, as well as instrument operator variability. Thus, generic reference ranges may not be applicable to individual centers and should be locally produced.…”
Section: Assay Interpretationmentioning
confidence: 99%
“…The results showed that the instruments are more interchangeable than originally reported [62]. However, there is still much debate as to what the appropriate initiators and parameters are to evaluate for consistent and reliable results [6366]. Currently, the variability requires multiple daily calibrations and trained personnel to limit the potential for user error.…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…[4][5][6][7] The disadvantages of viscoelastic hemostatic assays have historically included a relatively high coefficient of variation, poorly standardized methodologies, and limitations on the specimen stability of native whole blood samples. [8][9][10] In the pediatric setting, an advantage of the TEG is the relatively small sample volume needed, but a disadvantage is the difference in reference ranges between infants, especially newborns, and adults. 10 A variety of assays containing different activators can be run on a TEG device, providing insights into different aspects of coagulation.…”
mentioning
confidence: 99%